solution of this one
Attachments:
![](https://hi-static.z-dn.net/files/dd5/9bdde0dbfcb9b58bd862648f905e50d2.jpg)
Answers
Answered by
0
1.)
In given limit
x tends to 2-
So x is nearer to 2 from left side...
So x - 2 will always be negative...
Thus modulus will be open as negative (x -2)
(x-2) will get cancel in numerator and denominator.
So answer is -1.
2.)
![= \frac{2x + 3}{ \sqrt{ {x}^{2} - 1 } } = \frac{2x + 3}{ \sqrt{ {x}^{2} - 1 } }](https://tex.z-dn.net/?f=+%3D+%5Cfrac%7B2x+%2B+3%7D%7B+%5Csqrt%7B+%7Bx%7D%5E%7B2%7D+-+1+%7D+%7D+)
![= \frac{2x + 3}{ x\sqrt{ 1 - \frac{1}{ {x}^{2} } } } = \frac{2x + 3}{ x\sqrt{ 1 - \frac{1}{ {x}^{2} } } }](https://tex.z-dn.net/?f=+%3D+%5Cfrac%7B2x+%2B+3%7D%7B+x%5Csqrt%7B+1+-+%5Cfrac%7B1%7D%7B+%7Bx%7D%5E%7B2%7D+%7D+%7D+%7D)
![= \frac{2 + (\frac{3}{x} )}{ \sqrt{ 1 - \frac{1}{ {x}^{2} } } } = \frac{2 + (\frac{3}{x} )}{ \sqrt{ 1 - \frac{1}{ {x}^{2} } } }](https://tex.z-dn.net/?f=+%3D+%5Cfrac%7B2+%2B+%28%5Cfrac%7B3%7D%7Bx%7D+%29%7D%7B+%5Csqrt%7B+1+-+%5Cfrac%7B1%7D%7B+%7Bx%7D%5E%7B2%7D+%7D+%7D+%7D)
Putting x tends to infinity we get,
![= \frac{2 + (0)}{ \sqrt{ 1 - 0 } } = \frac{2 + (0)}{ \sqrt{ 1 - 0 } }](https://tex.z-dn.net/?f=+%3D+%5Cfrac%7B2+%2B+%280%29%7D%7B+%5Csqrt%7B+1+-+0+%7D+%7D)
In given limit
x tends to 2-
So x is nearer to 2 from left side...
So x - 2 will always be negative...
Thus modulus will be open as negative (x -2)
(x-2) will get cancel in numerator and denominator.
So answer is -1.
2.)
Putting x tends to infinity we get,
Similar questions